Morphological investigations of the surface epithelium of ductuli efferentes of black isogenic mice (Mus musculus) - Orsi, A. M.; Matheus, SMM; Gregorio, E. A.; Beu, CCL (Blackwell Wissenschafts Verlag Gmbh, 1998)
Morphological investigations of the epithelial cell types that line the ductuli efferentes (DE) of black isogenic mice confirm absorption of the luminal fluid phase by endocytosis as the main function of ductuli efferentes (DE) in this species. :Furthermore, all the histochemical and ultrastructural observations on the DE epithelial histoarchitecture indicate other cellular functions such as exocytosis and probably secretion: including an aprocrine secretory process.